Lineament mapping in Malaysian tropical forest environment utilizing Landsat imagery - Yusof, Norhakim (2009)
The remote sensing application of multispectral data analysis has been proven as a useful tool in geological exploration especially in lineament identification and mapping. This study demonstrates the use of multispectral Landsat TM and ETM+ satellite data obtained in different two acquisition dates in year 1990 and 2002 for lineament interpretation in a Malaysian tropical forest environment. The Digital Elevation Model (DEM) was also been utilized to improve the interpretation process. Utilizing the rose diagram analysis and histogram superimposition, it was found that most of the major orientations from field station were successfully matched with the orientations from extracted lineaments obtained from the imageries. The lineaments also found to be structurally controlled by the river segments. Thus river segments may be used as a basis in the early stage of interpretation where the knowledge of general lineament trend is necessary. The results from the study showed that remote sensing technique through the manual extraction is capable of extracting lineament trends in tropical forest which inaccessible by conventional survey technique. The undertaken steps may be utilized as an ideal framework of lineaments extraction utilizing the Landsat imagery in tropical forest environment such as Malaysia.